PUBLIC POLICY IMPLEMENTATION: CHALLENGES AND SOLUTIONS IN ACHIEVING PEOPLE'S WELFARE - Yunika Depri Listiana; Jackson Yumame; Melyana R Pugu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The implementation of public policy is a complex process and faces various challenges, including limited resources, social resistance, and the need for coordination between institutions. This challenge demands a holistic approach that involves the active participation of the community and synergy between policy and local needs. This study explores various solutions to overcome obstacles in the implementation of public policies, such as the importance of data-based policies, effective communication, the provision of adequate resources, and continuous monitoring and evaluation. In addition, strong leadership and commitment from all stakeholders play a key role in the successful implementation of policies. With an integrated approach and collective support, the main goal of achieving people's welfare can be realised effectively and sustainably.